2015
DOI: 10.1371/journal.pone.0125378
|View full text |Cite
|
Sign up to set email alerts
|

Aggregated Clumps of Lithistid Sponges: A Singular, Reef-Like Bathyal Habitat with Relevant Paleontological Connections

Abstract: The advent of deep-sea exploration using video cameras has uncovered extensive sponge aggregations in virtually all oceans. Yet, a distinct type is herein reported from the Mediterranean: a monospecific reef-like formation built by the lithistid demosponge Leiodermatium pfeifferae. Erect, plate-like individuals (up to 80 cm) form bulky clumps, making up to 1.8 m high mounds (1.14 m on average) on the bottom, at a 760 m-deep seamount named SSS. The siliceous skeletal frameworks of the lithistids persist after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 49 publications
4
43
0
Order By: Relevance
“…The interpretation is of a radiolarian driven DSi depletion of the surface ocean. The link between sponge distributions and DSi stems from the implicit assumption that siliceous sponges are unable to thrive at low DSi (e.g., Maldonado et al, 1999;Ritterbush et al, 2015), although siliceous sponge reefs in the modern oceans are still forming in some areas despite the relatively low DSi concentrations (10-40 µM) (Uriz, 2006;Chu and Leys, 2010;Maldonado et al, 2015). The modern day global distribution of sponges suggests that sponges are adapted to a great range of DSi conditions and the presence of sponges in the stratigraphic record must be treated cautiously (Alvarez et al, 2017).…”
Section: Biosilicification In the Paleozoic Oceansmentioning
confidence: 99%
See 1 more Smart Citation
“…The interpretation is of a radiolarian driven DSi depletion of the surface ocean. The link between sponge distributions and DSi stems from the implicit assumption that siliceous sponges are unable to thrive at low DSi (e.g., Maldonado et al, 1999;Ritterbush et al, 2015), although siliceous sponge reefs in the modern oceans are still forming in some areas despite the relatively low DSi concentrations (10-40 µM) (Uriz, 2006;Chu and Leys, 2010;Maldonado et al, 2015). The modern day global distribution of sponges suggests that sponges are adapted to a great range of DSi conditions and the presence of sponges in the stratigraphic record must be treated cautiously (Alvarez et al, 2017).…”
Section: Biosilicification In the Paleozoic Oceansmentioning
confidence: 99%
“…Maldonado et al (1999) suggested declines in reef building sponges occurred at the Cretaceous-Tertiary boundary because of DSi limitation as diatoms evolved. However, highly siliceous sponge reefs are still forming in selected areas of the modern oceans despite the relatively low DSi concentrations (Uriz, 2006;Chu and Leys, 2010;Maldonado et al, 2015). There are certainly other factors, such as food availability and ocean temperature (Kahn et al, 2012) that control the abundance and biosilicification of sponges (Alvarez et al, 2017).…”
Section: Formation Of Chert Depositsmentioning
confidence: 99%
“…Although lithistids were significant members of Paleozoic and Jurassic reefs, they appeared unable to develop analogous aggregations in the modern ocean. This view has been challenged by the discovery of a monospecific reef-like formation around the top of a deep seamount at 800 m in the Mediterranean Sea (Maldonado et al 2015). Individuals of the foliose species Leiodermatium pfeifferae, which grows as erect, contorted, 0.3-0.9 cm thick plates, up to about 80 cm in height, and 100 cm in width (Fig.…”
Section: Lithistid Aggregationsmentioning
confidence: 99%
“…In the Northeast Atlantic (NEA), the current state of knowledge on lithistid sponges is mainly restricted to the Macaronesian islands. So far, 17 species have been described and recorded from the Azores (Carvalho & Pisera, 2019;Gray, 1859;Topsent, 1928Topsent, , 1904Topsent, , 1898Topsent, , 1892, Madeira and Selvagens (Bowerbank, 1869;Carter, 1873;Carvalho & Pisera, 2019;Johnson, 1863), Canary Islands (Carvalho & Pisera, 2019;Cruz, 2002;Topsent, 1892), Portugal mainland (Schmidt, 1870) and Morocco (Lendenfeld, 1907), whereas in the Mediterranean Sea, 15 species have been reported (Maldonado et al, 2015;Manconi, Serusi & Pisera, 2006;Manconi & Serusi, 2008;Perez et al, 2004;Pisera & Vacelet, 2011;Pulitzer-Finali, 1972;Vacelet, 1969). They are commonly found on hard substrate at 110-1,700 m depth (Carter, 1873;Carvalho, Pomponi & Xavier, 2015;Topsent, 1928), whereas in the Mediterranean Sea they usually occur in shallower waters or in cave systems (Manconi & Serusi, 2008;Pisera & Vacelet, 2011).…”
Section: Introductionmentioning
confidence: 99%